Noncanonical Alternative Polyadenylation Contributes to Gene Regulation in Response to Hypoxia. Issue 6 (30th May 2017) - de Lorenzo, Laura; Sorenson, Reed; Bailey-Serres, Julia; Hunt, Arthur G.
Abstract : Stress affects the production and fate of alternative mRNA isoforms to coordinate and fine-tune the adaptation of plants to the environment. Abstract: Stresses from various environmental challenges continually confront plants, and their responses are important for growth and survival. One molecular response to such challenges involves the alternative polyadenylation of mRNA. In plants, it is unclear how stress affects the production and fate of alternative mRNA isoforms. Using a genome-scale approach, we show that in Arabidopsis thaliana, hypoxia leads to increases in the number of mRNA isoforms with polyadenylated 3′ ends that map to 5′-untranslated regions (UTRs), introns, and protein-coding regions. RNAs with 3′ ends within protein-coding regions and introns were less stable than mRNAs that end at 3′-UTR poly(A) sites. Additionally, these RNA isoforms were underrepresented in polysomes isolated from control and hypoxic plants. By contrast, mRNA isoforms with 3′ ends that lie within annotated 5′-UTRs were overrepresented in polysomes and were as stable as canonical mRNA isoforms. These results indicate that the generation of noncanonical mRNA isoforms is an important feature of the abiotic stress response. The finding that several noncanonical mRNA isoforms are relatively unstable suggests that the production of non-stop and intronic mRNA isoforms may represent a form of negative regulation in plants, providing a conceptual link with mechanisms that generate these isoforms (such as alternative polyadenylation) and RNA surveillance.